Social, Emotional, and Behavioral Skills: An Integrative Model of the Skills Associated With Success During Adolescence and Across the Life Span - Napolitano, Christopher M.; Sewell, Madison N.; Yoon, Hee J.; Soto, Christopher J.; Roberts, Brent. W. (Frontiers in Education, 2021)
Social, emotional, and behavior (SEB) skills encompass a wide range of competencies related to how individuals build and maintain relationships, understand and manage emotions, pursue goals, and learn from experience. Despite near-consensus on the importance of SEB skills for success in life, there are numerous frameworks that simultaneously converge and diverge in how they define and measure SEB skills. In this article, we discuss our integrative model encompassing five broad skill domains: Self-Management, Innovation, Social Engagement, Cooperation, and Emotional Resilience Skills (Soto, Napolitano, & Roberts, 2021). Our model defines SEB skills as skills (i.e., what someone is capable of doing) and not traits (i.e., what someone tends to do). Using this definition and model as a foundation, we argue for the importance of investigating SEB skill development during adolescence, a period where SEB skills may be both particularly amenable to change and particularly predictive of life outcomes. In particular, we highlight how SEB skills allow adolescents to take advantage of the new opportunities afforded to them as they make major cognitive and social transitions.